EVALUATION OF THE 150 KV PMT CONTACT SIMULTANEITY TEST FOR TRANSFORMER BAY 3, LOMANIS SUBSTATION - Arsiandro, Fadzly Haris Arsiandro; Nasrulloh; Mubarok, Rizky; Rizki Noor Prasetyono (Program Studi Teknik Elektro Universitas Peradaban, 2025)
Circuit Breaker (PMT) is an important equipment in the electric power system that functions to break and connect the current both under normal conditions and when a disturbance occurs, so that the reliability and safety of the system are highly dependent on the quality of the operation of this device. One of the critical parameters that must be met is the simultaneity of inter-phase contacts so that transient conditions, overvoltages, and unbalances can be minimized. This study aims to determine the results of the simultaneity test on the 150 kV PMT Bay Transformer 3 Lomanis Substation to assess the reliability of its operation and its compliance with technical standards. The test method is carried out through simultaneity analysis based on the results of measurements of inter-phase contact operation time in open trip and close conditions, as well as statistical analysis using the One-Sample T-Test test through SPSS software. The measurement results show that the highest inter-phase time difference only reaches 0.90 ms, far below the SKDIR 0520 standard limit of 10 ms. Statistical test results support these findings, with the Time Open Trip parameter having an average of 27.9833 ms with a significance level of 0.910 (p > 0.05) and the Time Close Trip having an average of 65.8000 ms with a significance level of 0.094 (p > 0.05). Both values ​​indicate no significant difference from the standard. Therefore, the PMT in Transformer Bay 3 of the Lomanis Substation is declared to be operating synchronously, reliably, within the required tolerance limits, and suitable for supporting power system reliability.